Solução para atualização de software do PIC24EP512GU810 via sistema bootloader e detector de entrada USB - Carvalho, Ana Carolina Hillmann de (2019)
This work presents the development of a bootloader system for software update on electronic boards through USB communication, thus eliminating the use of conventional microcontroller recorders. For a good implementation of this solution it is necessary to understand and develop methods of partitioning the microcontroller flash memory, interpret and perform data separation in Intel Hex file format, among other relevant steps for its completion. The proposal in question emerged as a solution to problems with recorders diagnosed by the company Saubern, located in the city of Campo Mourão - PR. For the implementation of this solution, the PIC24EP512GU810 was used as its main component, as it has enough memory for its realization, support for USB communication and also because it is compatible with the PIC currently used by the company. The results showed that the implemented solution made it possible to update the software more simply by using only one USB data device.